Bahasa Inggris - Puri Kusuma Dwi Putri; Devi Purnamasari; Zahrotul Umami (Universitas Pendidikan Nasional, 2023)
This study discusses the tourism potential of one of the villages in Semarang Regency, namely Kemambang Village, Banyu Biru District, Ambarawa, Central Java Province. The existence of tourism potential in Kemambang Village requires special attention from the government and local communities on the importance of marketing communication knowledge in the development of tourism ecology, the application of place making as well as an understanding of the assets owned by each region and the application of spatial practices. The aim of the study was to explore the implementation of communication in the planning and development of tourism ecology and place-making in Kemambang village, Ambarawa, Central Java province. This study employed a qualitative research design method to explore how the concept of creative communication in the digital era can be understood and carried out in the creative communication industry from the perspective of the main stakeholders and uses a case study approach. Data analysis was conducted by reducing data, displaying data, and drawing conclusions. The result of the research show that Kemambang Village has a lot of tourism potential that has not been exposed and optimized due to the lack of awareness of the people of Kemambang Village in understanding the importance of communication for tourism ecology development, place-making, asset needs, and the application of spatial practices in Kemambang.